A call for broadening the range of approaches to case studies in purchasing and supply management. Issue 4 (December 2016) - Dubois, Anna; Salmi, Asta
Abstract: Case studies are frequently adopted in purchasing and supply management studies, but the field would benefit from more diversified approaches to this method of scientific inquiry. The inherently flexible case study approach allows for benefiting from the often serendipitous features and non-linear, interactive patterns of scientific work. We urge scholars to be open about their research paths and pay more attention on reflection and learning aspects of case studies. Furthermore, problematisation rather than gap-spotting can serve as a fruitful grounding for formulation of research questions. The academic community can contribute to diversity by supporting and legitimizing different approaches to case studies, as long as these approaches are well grounded and argued for. Highlights: PSM field benefits from developing the variety of case study approaches. Positivistic views to case studies still dominate, but novel approaches are appearing. Non-linear approaches emphasize and make explicit the processes of case studies. The view of case research as an emergent and flexible process acknowledges learning and problematisation. We urge scholars to reflect upon their research processes and make them more visible.